Ultrasonic-Assisted Semi-Bionic Extraction of Tannins from Wild Persimmon Leaves - Yu1, Xianchun; Sun2, Delin; Fu1, Xijun; Zhou1, Sirou (Asian Journal of Chemistry, 2013)
Tannin was extracted from wild persimmon leaves (Diospyros kaki L.f ) using the ultrasonic-assisted semi-bionic approach. Infrared spectrum analysis showed that tannins from wild persimmon leaves contain many proanthocyanidin-like substances with 3-O-gallate acyl structure. Free radical scavenging capacity assay showed that the ultrasonic-assisted semi-bionic approach can improve the scavenging activity of tannins on radicals, including OH•, DPPH• and ABTS•+. The half maximal inhibitory concentration values were reduced by 0.62, 0.116 and 1.19 mg mL-1, respectively, compared with the water reflux extraction method. Experimental results of orthogonal optimization showed that the tannin extraction quantity can reach 226.8 mg g-1, which was much higher than the sample obtained without ultrasonic assistance under the following experimental conditions: pH values of 1.8, 7.5 and 8.4, respectively; 50 % solvent mass fraction; 35 min extraction time; 50 ºC extraction temperature; 300 W ultrasonic power and 30 KHz ultrasonic frequency. These results suggested that this method could increase the activity and extraction yield of tannins.